Epidemiology of strabismus surgery in a public hospital of the Brazilian Federal District - Juliana Tessari Dias Rohr (Revista Brasileira de Oftalmologia)
Abstract Purpose: to determine the prevalence of different types of strabismus submitted to a surgical procedure in a public hospital in the Brazilian Federal District. Methods: Retrospective cross-sectional review of medical records of patients who underwent strabismus surgery performed by the same surgeon from 2004 to 2014. Incomplete records were excluded from the study. Variables included sex, age, type of strabismus, type of surgery, and re-surgeries. Strabismus was classified into three main types (esotropia, exotropia, and pure vertical deviation), and their subtypes. The type of surgery was determined by the number of muscles operated on (up to two, or more than two), the involvement of oblique and vertical rectus muscles, and muscle displacement. Results: 563 patients were reviewed and 531 were included in the study. The average age was 12.7 years, and females accounted for 54.4% of total patients. Esotropia was the most frequent type of strabismus (74%), followed by exotropia (23.7%) and pure vertical deviation (2.3%). The most frequent subtype of esotropia was infantile (49.1%), with 16.1% of these surgeries performed before the age of 2. Constant exotropia was the most frequent subtype of exotropia (27.8%). The prevalence of esotropia decreased with age, whereas that of exotropia increased. 52.3% of surgeries involved more than two muscles. An association between different types of deviation was found in 58.9% of patients. In cases of paralytic strabismus, the sixth nerve was the most affected (46%). Re-surgeries accounted for 10.7% of total surgeries. Conclusion s: Esotropias were the most common types of strabismus, especially infantile esotropia. Most cases were associated with other types of deviation, and needed more complex surgeries, involving more than two muscles. This study expects to contribute to the planning of health measures that may effectively improve the assistance provided to the population.